Field Massage Therapy terhadap Stabilitas Fisiologis dan Kadar Bilirubin Bayi dengan Hiperbilirubinemia - Wahyuni, Fitri; Rahmayanti, Rini (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of field massage therapy on the physiological stability and bilirubin levels of babies with hyperbilirubinemia. The method used is quantitative with a one-group post-test research design. The study's results showed that the average bilirubin level of babies after the intervention was given was 10.6 mg/dL. The statistical analysis found that the p-value was 0.000, which means there was an influence from the therapy provided. This research concluded that there were differences in the impact on physiological stability and bilirubin levels before and after being given field massage therapy. Keywords: Field Massage Therapy, Hyperbilirubinemia, Neonates